Saber local, narrativas nacionais, movimentos étnicos - Faulhaber, Priscila (Cadernos de Linguagem e Sociedade, 2010)
In this paper, Indigenous territorial claims are examined through historical and ethnological documents, focusing on the discourse of these movements, which are based on the Brazilian national social imaginary. The communicative acts performed at Indigenous assemblies imply the emergence of a representation crisis imposed by the dominant political system, such that not all Indian leaders are deemed legitimate, and their leadership is questioned in the process of political participation and affirmation of collective identity. This crisis is figured in the social imaginary which establishes native representations, in which the Cobra Norato serves as a significant example. It is argued that this symbol is a local expression of national culture.